2021
DOI: 10.1007/s10796-021-10226-5
|View full text |Cite
|
Sign up to set email alerts
|

Voice Assistant vs. Chatbot – Examining the Fit Between Conversational Agents’ Interaction Modalities and Information Search Tasks

Abstract: Owing to technological advancements in artificial intelligence, voice assistants (VAs) offer speech as a new interaction modality. Compared to text-based interaction, speech is natural and intuitive, which is why companies use VAs in customer service. However, we do not yet know for which kinds of tasks speech is beneficial. Drawing on task-technology fit theory, we present a research model to examine the applicability of VAs to different tasks. To test this model, we conducted a laboratory experiment with 116… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 81 publications
2
27
0
Order By: Relevance
“…In contrast, prior work focusing on voice as an output examined predominantly questions related to how much people trust a recommendation that is delivered verbally (vs. in written form) by a voice-based interface (Qiu & Benbesat, 2005). Only few studies examined a fully conversational interaction that required both the voice input by the user and a verbal response by the system (see Rzepka et al, 2021). Second, the type of boundary conditions typically examined either appearance-related factors (e.g., predominantly the presence of avatars; see Hess et al, 2009;Qiu & Benbasat, 2009) or broad consumer characteristics (e.g., consumers' general privacy concerns or emotional attachment tendencies; see Pagani et al, 2019;Son & Oh, 2018).…”
Section: Related Prior Work On Voice-based Interfacesmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, prior work focusing on voice as an output examined predominantly questions related to how much people trust a recommendation that is delivered verbally (vs. in written form) by a voice-based interface (Qiu & Benbesat, 2005). Only few studies examined a fully conversational interaction that required both the voice input by the user and a verbal response by the system (see Rzepka et al, 2021). Second, the type of boundary conditions typically examined either appearance-related factors (e.g., predominantly the presence of avatars; see Hess et al, 2009;Qiu & Benbasat, 2009) or broad consumer characteristics (e.g., consumers' general privacy concerns or emotional attachment tendencies; see Pagani et al, 2019;Son & Oh, 2018).…”
Section: Related Prior Work On Voice-based Interfacesmentioning
confidence: 99%
“…Second, the type of boundary conditions typically examined either appearance-related factors (e.g., predominantly the presence of avatars; see Hess et al, 2009;Qiu & Benbasat, 2009) or broad consumer characteristics (e.g., consumers' general privacy concerns or emotional attachment tendencies; see Pagani et al, 2019;Son & Oh, 2018). Except for emerging work examining the task characteristics as possible boundary conditions (Rzepka et al, 2021), no prior work we are aware of examined the unique conversational design characteristics during an interaction such as the specific semantic properties of the language or how the conversation itself is structured. Third, the type of outcomes studied in earlier work focused predominantly on perception outcomes (such as trust or satisfaction measures; Hess et al, 2009;Pagani et al, 2019;Qiu & Benbasat, 2009;Qiu & Benbesat, 2005) as opposed to the evaluation of the firm or downstream behavioral outcomes (see Son & Oh, 2018 for an important exception).…”
Section: Related Prior Work On Voice-based Interfacesmentioning
confidence: 99%
See 2 more Smart Citations
“…Text and voice interaction modalities are particularly relevant to our work. A comparative study of voice and text-based interaction with chatbots [57] found that voice was generally preferred in terms of cognitive effort, enjoyment, efficiency, and satisfaction, but this was influenced by goal-directedness of the task.…”
Section: Analytical Chatbotsmentioning
confidence: 99%